(untitled) (Pauta Geral - Estudos em Jornalismo, 2020)
Professor Maxwell McCombs began his career as a journalist in the 1960s, as a reporter for the New Orleans Times. A decade later, McCombs, in partnership with Donald Shaw, developed one of his major theories - the agenda-setting hypothesis, now considered a theory, which reflects on the influence of the mass media in relation to public affairs. In the 1980s, McCombs became a professor in the Journalism Department at the University of Texas. In this interview, we seek to recover the basis of the Agenda-setting theory and confront the initial hypothesis with the contemporary scenario and the advent of the internet, contextualizing particularities of Brazilian politics and electoral process and seeking to reflect on the possibility of scheduling different media, especially TV. McCombs was emphatic in saying that the media agenda plays an important ethical role "to use time and space for important topics and not fun topics."